PENYEBAB PENURUNAN MEASURED GAS TEMPERATURE (MGT) MARGIN ENGINE ARRIUS 2R PADA HELIKOPTER BELL 505 JET RANGER X MENGGUNAKAN METODE FAULT TREE ANALYSIS (FTA) - Angga Nur Cahyadi; Edi Sofyan; Erwan Eko Prasetiyo (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
The aviation industry has recovered from the pandemic, and airlines are confidently operating their fleets again, one of which is the Bell 505 helicopter. Helicopter maintenance is also carried out to maintain performance in good condition and ready to fly. The performance of the Bell 505 helicopter is also influenced by the condition of the engine, if the engine is said to have good performance, the engine must be able to be used in function according to the planned time. In Bell 505, a problem was found during the implementation of the Power Assurance Check, namely, the decrease in the MGT margin value which is close to the value of 0, resulting in a decrease in the performance of the engine itself. Therefore, analysis and corrective action are needed to determine the cause of the decrease in the MGT margin of the Arrius 2R engine. The method used is fault tree analysis, by taking a top down approach, starting with the assumption of failure from the Top Event then detailing down to the basic failure (Root Cause). After drawing the FTA construction, evaluation is carried out with the Minimum Cut Set until the basic event is obtained. The results of the analysis conducted with “Decrease in MGT Margin Engine Arrius 2R